Bilingual Environmental Awareness (BEA) in Pesantren for Enhancing Speaking Skill - Hari Prastyo; Ika Irmawansah; Imam Wahyudi (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2023)
Bilingual Environmental Awareness (BEA) which is implemented at certain community is mostly taken place in Pesantren. This article tried to investigate the steps in implementing Bilingual Environmental Awareness (BEA) at Pesantren to enhance speaking skill. It was kind of research that used Snapshot Exploratory Case Study. The subject of this research was students and teachers of pesantren of Al Multazam Mojokerto. The result showed that (1) To implement Bilingual Environmental Awareness (BEA) at Pesantren environment should combine Teaching-Learning Activities and Language Usage. Teaching and Learning Activities includes Drilling, Explaining, Immitation, Questioning and Answering, Modeling, Making Dialogue, Practicing, Giving Feedback, and Concluding. Then (2) Language Usage (LU) includes Language Acquisition and Language Environment. In addition, (3) The combination of Teaching-Learning Activities and Language Usage which were integrated could enhance speaking skill at Pesantren environment.